1989
DOI: 10.1038/bjc.1989.316
|View full text |Cite
|
Sign up to set email alerts
|

Papillary and follicular thyroid carcinomas show a different pattern of ras oncogene mutation

Abstract: In a small initial study of oncogene activation in differentiated thyroid cancer, using DNA transfection and tumorigenicity assays, we identified activating ras mutations in 80% (4/5) of follicular carcinomas, but in only 20% (2/10) of papillary carcinomas (Lemoine et al., 1988). However, Suarez et al. (1988), using the 'focus' transformation assay, reported two out of a total of three papillary carcinomas to have activated ras oncogenes, while Fusco et al. (1987), also using DNA transfection techniques, faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 6 publications
1
63
1
1
Order By: Relevance
“…Wright et al (1989) found 3/17 (17%) of papillary carcinomas (which classically arise de novo), contained ras mutations compared to 8/15 (53%) of follicular carcinomas which arise through an adenoma-carcinoma sequence; this difference is statistically significant (2 = 4.95 P <0.05). The difference in the prevalence of ras mutations found between carcinomas arising from dysplasia as opposed to origin from adenomas in both colorectal and thyroid tumours may also become apparent in other tumour systems, and suggests that molecular changes may underlie morphological abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Wright et al (1989) found 3/17 (17%) of papillary carcinomas (which classically arise de novo), contained ras mutations compared to 8/15 (53%) of follicular carcinomas which arise through an adenoma-carcinoma sequence; this difference is statistically significant (2 = 4.95 P <0.05). The difference in the prevalence of ras mutations found between carcinomas arising from dysplasia as opposed to origin from adenomas in both colorectal and thyroid tumours may also become apparent in other tumour systems, and suggests that molecular changes may underlie morphological abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…In papillary carcinomas, Ha-ras codon 12 mutations were found in 4 of 66 (6%) cases. Suarez et al (20) and Du Villard et al (7) found a high frequency of mutations: 50% and 44% of cases respectively, (Table 3), but Wright et al (6) and Manenti et al (13) observed no mutations in these cancers. In eight cases of undifferentiated carcinomas, we detected no point mutation of Ha-ras, in agreement with the findings of Suarez et al (20) and Du Villard et al (7).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the ras (Ha-, Ki-, N-ras) proto-oncogene have been reported in 20-60% of thyroid tumours, particularly in follicular types (3,5,6,15,17), and more frequently in iodine-deficient areas (16). For this reason, ras mutations have been suggested as an important pronostic marker for thyroid cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In myeloid leukemia the chronic phase is characterized by loss of proliferation control but maintenance of di erentiation capacity, while the conversion to the acute, blastic phase is associated with loss of di erentiation capacity (Champlin and Golde, 1985) and, in 50 ± 60% of the cases, mutation in the TP53 gene (Feinstein et al, 1991). In thyroid, the relatively benign, well di erentiated carcinomas do not present TP53 mutations, which are only found in the aggressive, anaplastic forms (Wright et al, 1991, reviewed in Fagin, 1994. Interestingly, a similar correlation has been also found in p53 knock-out mice where chromosomal abnormalities and anaplastic phenotypes are more frequent and severe in p53 7/7 mice than in wild type mice (Kemp et al, 1993;Venkatachalam et al, 1998).…”
mentioning
confidence: 99%